Neuronostatin, a Novel Peptide Encoded by Somatostatin Gene, Regulates Cardiac Contractile Function and Cardiomyocyte Survival - Vainio, Laura (American Society for Biochemistry and Molecular Biology, 2012)
Neuronostatin, a recently discovered peptide encoded by somatostatin gene, is involved in regulation of neuronal function, blood pressure, food intake, and drinking behavior. However, the biological effects of neuronostatin on cardiac myocytes are not known, and the intracellular signaling mechanisms induced by neuronostatin remain unidentified. We analyzed the effect of neuronostatin in isolated perfused rat hearts and in cultured primary cardiomyocytes. Neuronostatin infusion alone had no effect on left ventricular (LV) contractile function or on isoprenaline- or preload-induced increase in cardiac contractility. However, infusion of neuronostatin significantly decreased the positive inotropic response to endothelin-1 (ET-1). This was associated with an increase in phosphorylation of p38 mitogen-activated protein kinase and c-Jun N-terminal kinase (JNK). Treatment of both neonatal and adult cardiomyocytes with neuronostatin resulted in reduced cardiomyocyte viability. Inhibition of JNK further increased the neuronostatin-induced cell death. We conclude that neuronostatin regulates cardiac contractile function and cardiomyocyte survival. Receptors for neuronostatin need to be identified to further characterize the biological functions of the peptide.